Are there sex differences in energy expenditure and enjoyment in older adults playing active video games?. (July 2022) - Ferreira, Juliana A.; Passos, Giselle S.; Youngstedt, Shawn D.; de Lima, Bráulio E.; Vieira, Lorraine B.; Martins, Marcelo M.; de Assis, Bernardo P.; Santana, Marcos G.
Abstract: The aim of this study was to compare sex differences in energy expenditure and enjoyment in older adults during Active Video Game activities and sedentary behavior (watching television). In a within-subjects design, n = 32 older adults were included (15 men and 17 women). Energy expenditure was measured during each activity using indirect calorimetry. Energy expenditure was expressed in J.kg −1 .min −1 and Metabolic Equivalents. Enjoyment was measured after each activity with the Physical Activity Enjoyment Scale. Energy expenditure was greater in Active Video Game activities compared to sedentary behavior in both men and women, but no differences were observed between sexes. The women reported greater enjoyment in Active Video Game activities compared to the men, and women reported greater enjoyment in Active Video Game activities compared to watching television, whereas the men did not report differences in enjoyment between Active Video Game vs. television watching. In conclusion, despite no difference in Energy expenditure, older women enjoy more than men playing Active Video Game, maybe they can be targeted for this intervention. (Clinical Trials Registration - NCT04352543).